Technological advancement and its impact on labour and capital in South Africa. - Coetzee, Gert Jacobus (My University, 2016)
Recent advances in digital technology have given machines the ability to perform tasks that until recently only humans have been able to do. Historically digital technology has been very bad when attempting certain tasks like speech recognition but have suddenly become very capable and even good. Several commentators have expressed concern that these new capabilities are making our ability to economise labour outstrip our ability to find new work for labour, leading to unemployment. The purpose of this exploratory study was to investigate the possibility that digital technology is advancing unemployment in South Africa by allowing capital to be substituted for labour. The research was performed by identifying companies that have been able to increase their productivity over the last five years while at the same time reducing their headcount. Senior people within these organisations were then interviewed to ascertain how their companies were able to achieve this feat. The findings indicate a small group of firms, which were put under pressure to improve their productivity, did so through the use of digital technology. The findings suggest that this group is leading the charge of South African companies who are using digital technology as a substitute for labour and that more companies are likely to follow suite in the future.
MBA
Keywords: Labor supply -- Effect of technological innovations on -- South Africa. Unemployment -- South Africa.